The development of mobile learning based physical fitness learning media in grade x high school students in Pasuruan Regency - Ali Mahfud; Siti Nurrochmah; Fahrial Amiq (CV Rezki Media, 2022)
This research aims to develop a mobile learning-based learning media based on physical fitness material for high school students in grade ten. The method used in this study is research and development. The data collection technique uses interviews with sports teachers and the distribution of questionnaires to grade ten students at Senior High School 1 Purwosari, Senior High School 1 Gondangwetan, and Senior High School 1 Lumbang. The data analysis technique in this study utilized a Likert scale which examined the gradation of the score. The products are firstly validated by experts, such as media, learning and material experts. The score results of each validator are 93% of the scores from the validation of media experts, 82% of the scores from the validation of learning experts, and 84% of the scores from the validation of material experts, while for large group trials, the score obtained is 85%. Thus, referring to the data results, the development of the product in this research is feasible, can be used and disseminated.